Perancangan Video Promosi Tempat Pariwisata Air Terjun Coban Sewu di Kabupaten Malang - Yonathan Sutawijaya (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2022)
Malang District is an area has good tourism potential. One of which is Coban Sewu waterfall located in the Ampelgading Sub-District, Malang District. Coban Sewu waterfall is the most beautiful waterfall on Java Island and Indonesia. However, based on the initial observation, the result is that the lack of local government efforts to introduce more widely on its tourism, so the need for a promotional video to introduce tourism potential contained in Coban Sewu waterfall. Using methods qualitative research methods and research strategies are qualitative descriptive, to produce a promotional video that is able to introduce tourism potential contained Coban Sewu waterfall on Malang District to prospective tourists, both domestic and foreign.